Lectotypification of the name Micromelum integerrimum (Rutaceae) - Singh, Rajeev Kumar (Phytotaxa, 2016)
The genus Micromelum Blume (1825: 137) consists of about nine species worldwide (Mabberley 2008), with only one species found in India (Nair & Nayar 1997), Micromelum integerrimum (Roxb. ex DC.) Wight & Arn. ex Voigt, based on Bergera integerrima Roxb. ex DC. During systematic study of this species in India, I realized some confusion in the authorship and the need for lectotypification. After a thorough examination of literature and type specimens at different herbaria, the authorship is clarified here, and a lectotype is designated, following the guidelines of Art. 9.2 of the Melbourne Code (McNeill et al. 2012).